Prospects for Predictable Dynamic Scheduling in RTDOS - Swim, B. R.; Benmaiza, M.; Taylı, Murat; Woodward, M. C. (IEE Proceedings Computer and Digital Techniques, 1997)
Future dynamic distributed hard real-time systems may control unpredictable environments and will need operating systems that can handle unknown and changing task populations. In this extreme case, not only is task scheduling totally dynamic, but the system's topology and architecture must adapt to unforeseen configurations. This paper addresses the difficult problem of dynamic task scheduling in a Real Time Distributed Operating System (RTDOS). RTDOS is unique because it possesses the potential to map, at execution time, a flexible topology of networked nodes onto a network of tasks. Attempts will be made to characterize the predictable adaptability of the scheduler so as to relax the pre-run-time scheduling requirements for an RTDOS application. A scheduler architecture and dynamic deadline guarantee scheme are presented along with some experimental results.